Femvertising and the Hedonic Motivation of Male Consumers: A New Perspective on Purchase Decisions for Men's Skincare Products - Ayuda, Fitrien; Hendriani, Susi; Wijayanto, Gatot; ., Samsir (Journal of Posthumanism, 2025)
This study investigates the influence of femvertising advertisements that challenge traditional gender norms on the purchase decisions of male consumers in the skincare market, with hedonic motivation as a mediating factor. Using a quantitative approach with 260 male respondents in Indonesia, the research integrates perspectives from Diffusion of Innovation Theory, Theory of Behavior Change, and Bourdieu’s Social Practice Theory. Findings reveal that visually and emotionally appealing femvertising fosters positive emotions and self-confidence, significantly impacting consumer purchasing behavior. The study provides theoretical contributions to gendered marketing literature and practical implications for marketing strategy design.